A Beginner’s Guide to Collecting Questing Hard Ticks (Acari: Ixodidae): A Standardized Tick Dragging Protocol - Jordan Salomon; Sarah A. Hamer; Andrea Swei (2020)
Tick-borne diseases are emerging globally, necessitating increased research and coordination of tick surveillance practices. The most widely used technique for active collection of host-seeking, human-biting tick vectors is 'tick dragging', by which a cloth is dragged across the top of the vegetation or forest floor and regularly checked for the presence of ticks. Use of variable dragging protocols limits the ability of researchers to combine data sets for comparative analyses or determine patterns and trends across different spatial and temporal scales. Standardization of tick drag collection and reporting methodology will greatly benefit the field of tick-pathogen studies. Based on the recommendations of the Center for Disease Control and Prevention and other ecological considerations, we propose that tick dragging should be conducted to sample at least 750 m2 along linear transects when habitat allows in a manner that reduces bias in the sampled area, and report density of each tick species and life stage separately. A protocol for constructing a standard drag cloth, establishing linear transects, and drag sampling is presented, along with a downloadable datasheet that can be modified to suit the needs of different projects. Efforts to align tick surveillance according to these standard best practices will help generate robust data on tick population biology.